PERANCANGAN DAN PENGEMBANGAN WEBSITE INOVATIF UNTUK OPTIMALISASI LAYANAN PERPUSTAKAAN UNIVERSITAS MUHAMMADIYAH BIMA - Sukran Golit (LPPM Universitas Abdurrab, 2026)
Libraries play a crucial role in supporting academic activities at universities. However, the current manual method of managing library services can lead to delays in accessing information, errors in data recording, and suboptimal services for users. This research aims to design and develop an innovative website to optimize services at the Muhammadiyah University of Bima Library. The Waterfall method used in system development consists of needs analysis, design, implementation, testing, and maintenance. The website was developed using PHP, MySQL, Bootstrap, and triggers to support automation in library data management. System testing was conducted using Black Box Testing and the System Usability Scale (SUS). The Black Box Testing results showed that all system functions operated as expected with a 100% success rate. Meanwhile, the SUS test results obtained a score of 73.6, which is included in the Good and Acceptable category, indicating that the system was well received by users. In addition, the survey results showed that 80% of respondents felt that the system had improved library services. Therefore, the developed website can support the digitization of library services and contribute to the management of library services at the Muhammadiyah University of Bima.